Bisnis ikan asin dan dampaknya terhadap kesejahteraan masyarakat Sungai Pauh Langsa Barat - Asyura; Mastura; Junaidi (FEBI IAIN Langsa, 2022)
The salted fish business is one of the businesses located in Gampong Sungai Pauh, West Langsa District, Langsa City. This study aims to determine the income and welfare of salted fish processing workers in Gampong Sungai Pauh, West Langsa District. This research is a field research with descriptive qualitative methods. The sample consisted of 15 people. Sources of data used are primary and secondary data obtained by data collection methods through observation, interviews, and documentation.With the salted fish processing, salted fish processing workers' income has increased slightly, so that the life of salted fish processing workers is helped economically, such as being able to eat three times a day, buying clothes even once a year. Salted fish processing workers can be categorized as not prosperous, but economically, salted fish processing workers are greatly helped, if before working in salted fish processing, salted fish processing workers can only eat once a day but after working in salted fish processing, salted fish processing workers can eat. three times a day, buy at least one set of clothes, repair the damaged walls of the house.